English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

Add *The numbers after the variable are exponents!

(14x+4)+(14x+19)
(13x2+20x+9)+(10x2+11x+19)
(4x7+8x2+20x)+(10x6+4x3-14x2)
(-13x6-19x4+7x2+4x)+(13x7+16)
(-14x2+17x+5)+(-18x2+7x-12)+(7x2-14x-16)+(-7x2-4x-17)

2007-01-27 09:25:33 · 4 answers · asked by katiekcat5 3 in Science & Mathematics Mathematics

4 answers

(14x+4)+(14x+19)
= 28x+23

(13x2+20x+9)+(10x2+11x+19)
=23x^2 +31x 28

(4x7+8x2+20x)+(10x6+4x3-14x2)
=4x^7 +10x^6 +4x^3 + -6x^2 +20x

(-13x6-19x4+7x2+4x)+(13x7+16)
=13x^7 -13x^6 -19x^4 +7x^2 +4x +16

(-14x2+17x+5)+(-18x2+7x-12)+(7...
+(-7x2-4x-17)
=-32x2+6x-40

2007-01-27 09:30:22 · answer #1 · answered by ~Zaiyonna's Mommy~ 3 · 0 0

usually the arithmetic operation between groups of expressions surrounded by parenthesis is either multiply or divide.
When the plus sign is the operation the parenthesis are superfluous. The expression results in exactly the same result whether they are taken into account or not. You may want to check what the original problems were.
(14x+4)+(14x+19)
=28x+23

(13x2+20x+9)+(10x2+11x+19)
=23x2+32x+28

(4x7+8x2+20x)+(10x6+4x3-14x2)
=4x7+10x6+4x3-6x2+20x

(-13x6-19x4+7x2+4x)+(13x7+16)
=13x7-13x6-19x4+7x2+4x+16

(-14x2+17x+5)+(-18x2+7x-12)+(7x2-14x-16)
+(-7x2-4x-17)
=-32x2+6x-40

2007-01-27 17:43:32 · answer #2 · answered by anonimous 6 · 0 0

(14x+4)+(14x+19)
= 28x+23

(13x2+20x+9)+(10x2+11x+19)
=23x^2 +31x 28

(4x7+8x2+20x)+(10x6+4x3-14x2)
=4x^7 +10x^6 +4x^3 + -6x^2 +20x

(-13x6-19x4+7x2+4x)+(13x7+16)
=13x^7 -13x^6 -19x^4 +7x^2 +4x +16

(-14x2+17x+5)+(-18x2+7x-12)+(7...
Sorry, the above is incomplete.

2007-01-27 17:36:04 · answer #3 · answered by ironduke8159 7 · 0 1

1. 28x +23
2. 23x^2 +31x +28
3. 4x^7 +10x^6 +4x^3-6x^2+20x
4. 13x^7-13x^6-19x^4+7x^2+4x+16
5.

2007-01-27 17:32:16 · answer #4 · answered by bruinfan 7 · 0 0

fedest.com, questions and answers